Coral Venom Toxins - Schmidt, Casey A.; Daly, Norelle L.; Wilson, David T. (Frontiers in Ecology and Evolution, 2019)
The phylum Cnidaria contains a wide variety of unique organisms that possess interesting adaptations evolved over many years to help them survive in a competitive environment. One of these adaptations is the presence of venom, which has been of particular interest for studies aimed at identifying novel drug leads and for understanding the mechanisms involved in envenomation. The potency of the venom varies significantly amongst cnidarians, and although corals are often overshadowed by the jellyfish and sea anemone toxins, they also possess a range of interesting bioactive compounds. In this mini-review, we provide an overview of the toxins present in corals, highlighting the diverse structures and bioactivities.